Knowledge and Perception of Calcium Intake among Students in University Technology MARA. - Fatimah Sham; Emad Shdaifat; Norhaini Majid; Fatin Khairudin; Nadzirah Zainol; Syafiqah Majid (Universiti Kebangsaan Malaysia, 2013)
Osteoporosis-related fractures have been recognized as a major health problem, particularly in the elderly with a high morbidity and mortality rate.The aims of the study were to identify knowledge and perception toward calcium intake among students at UiTM and to explore the differences between genders in dietary calcium intake.